2020
DOI: 10.11604/pamj.2020.36.37.19046
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and barriers to HIV service uptake and delivery along the HIV care cascade in Cameroon

Abstract: Introduction The year 2017 marked a transition period with the end of the implementation of Cameroon´s 2014-2017 HIV/AIDS National Strategic Plan (NSP) and the development of the 2018-2022 NSP. We assessed barriers and challenges to service delivery and uptake along the HIV care cascade in Cameroon to inform decision making within the framework of the new NSP, to achieve the UNAIDS 90-90-90 target. Methods We conducted a cross sectional descriptive study nationwide, enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
(21 reference statements)
0
13
1
Order By: Relevance
“…Research has identified many challenges that disrupt HIV care at multiple levels, including at the individual, societal, and health systems levels. For example, factors range from denial of infection or HIV's existence, refusal to get tested, refusal to take ART, fear of breach of confidentiality, stigma, discrimination, racism, and poverty, to stock-outs of HIV tests and viral load testing reagents [6][7][8].…”
mentioning
confidence: 99%
“…Research has identified many challenges that disrupt HIV care at multiple levels, including at the individual, societal, and health systems levels. For example, factors range from denial of infection or HIV's existence, refusal to get tested, refusal to take ART, fear of breach of confidentiality, stigma, discrimination, racism, and poverty, to stock-outs of HIV tests and viral load testing reagents [6][7][8].…”
mentioning
confidence: 99%
“…Viral load testing is of utmost importance in determining the progress of treatment, identifying therapy failure and evaluating the risk for transmission. Meka et al ( 2020 ) found the barriers to viral load testing to be both at health care system and patient level. Ignorance, stock shortages of tests and staff shortages among others were identified as barriers to viral load testing (Meka et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meka et al ( 2020 ) found the barriers to viral load testing to be both at health care system and patient level. Ignorance, stock shortages of tests and staff shortages among others were identified as barriers to viral load testing (Meka et al 2020 ). Furthermore, the NDoH guidelines only describe the use of CD4 count monitoring to determine susceptibility to opportunistic infections and the need for possible prophylactic treatment (NDoH 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Documented multi-level barriers to pediatric HTS delivery and uptake include fear of a positive test, an inaccurate perception of risk, challenges with paternal consent, school schedules and logistical barriers, including the perceived costs of testing and care 15,16,17 . In our study, providers described nancial and logistical barriers experienced by caregivers to travel to the health facility for child testing and by HCWs and CHWs to deliver community-based testing.…”
Section: Discussionmentioning
confidence: 99%